FORMATION OF VILLAGE REGULATIONS ON LEGAL AID SERVICES FOR THE UNDERPRIVILEGED COMMUNITY IN BETIMUS MBARU VILLAGE SIBOLANGIT DISTRICT, DELI SERDANG REGENCY - Rolib Sitorus; Japansen Sinaga; Joy Zaman Felix Saragih; Ricky Banke; Tonggo Michael Sihombing (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Access to justice is a basic right of every citizen as guaranteed in Article 28D paragraph (1) of the 1945 Constitution of the Republic of Indonesia. However, in practice, underprivileged community groups in rural areas still face various structural and cultural obstacles in obtaining legal aid services. Betimus Mbaru Village, located in Sibolangit District, Deli Serdang Regency, is one of the areas facing similar challenges, with a low level of legal literacy among the community and a minimal number of legal aid institutions operating actively in the area. This condition shows the importance of local-based initiatives to guarantee the constitutional rights of village residents, one of which is through the formation of Village Regulations (Perdes) on Legal Aid Services. This study aims to analyze the urgency, mechanisms, and impacts of the formation of Perdes that regulates legal aid services for underprivileged communities. The approach used in this study is a juridical-empirical approach, with qualitative methods. Data were obtained through literature studies, in-depth interviews with village officials, community leaders, and underprivileged residents, and participatory observation in the village deliberation process. The collected data were analyzed descriptively-analystically by referring to applicable legal principles, as well as the theory of social justice and community legal empowerment. This research is expected to provide practical contributions to village government in realizing inclusive governance and oriented towards human rights. In addition, this research can be an initial reference for other regions with similar social characteristics in developing local policies for legal aid services.